EyeRis Shield: Eye Care Website - Annadurai, Vedhanahyakee; HAFIT, HANAYANTI (Applied Information Technology And Computer Science, 2025)
Eye care is essential in overall health care, as our vision allows us to perform daily activities independently. It is important to get regular eye check-ups to maintain healthy eyesight. However, rising of digital devices causes people exposed to extensive screen time which can lead to progressive vision deterioration. Despite this problem, accessible tools for reducing screen-induced eye strain remain limited. This issue often results in neglecting eye strain indications due to insufficient awareness of eye care. Therefore, the EyeRis Shield Website is proposed to self-detect vision disorders and provide eye care tools. Prototyping methodology is implemented to develop this website. The prototype is built using the Windows platform via Visual Studio Code. The tested prototype results in each actor successfully linked with their respective module. This application is expected to serve as an eye health resource for early detection of eye conditions and foster healthy eye care habits.